(untitled) (mathematica didactica, 2014)
The goal of the study presented in this article is to identify epistemic beliefs about mathematics as a scientific discipline with a focus on certainty of knowledge. The topic is discussed from both a psychological point of view and from the philosophy of mathematics. An interview study was conducted to investigate on the question whether domain-general conceptualizations of the certainty dimension are applicable to the domain mathematics. The recorded positions and arguments ask for a domain-specific conceptualization of certainty.